Return Words and Recurrence Function of a Class of Infinite Words - L’. Balková (Acta Polytechnica, 2007)
Many combinatorial and arithmetical properties have been studied for infinite words ub associated with ß-integers. Here, new results describing return words and recurrence function for a special case of ub will be presented. The methods used here can be applied to more general infinite words, but the description then becomes rather technical.